Systematic Literature Review: Efektivitas Pembelajaran Berpendekatan Konstruktivisme Dalam Meningkatkan Komunikasi Matematis Siswa - Dana, I Gusti Kade Krisna; Sudiarta, I Gusti Putu (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This Systematic Literature Review (SLR) examines the effectiveness of constructivist approaches in enhancing students' mathematical communication skills. Following the PRISMA protocol, seven relevant articles published between 2020 and 2025 were analyzed. The findings indicate that constructivist learning significantly improves mathematical communication across various educational levels through models such as contextual learning, problem-based learning, and interactive multimedia. Key characteristics include active student participation, social interaction, and the teacher's role as a facilitator. Supporting factors for this effectiveness include student collaboration and innovative media usage, whereas traditional models and unfavorable external factors serve as primary constraints. It is recommended that educators optimize the implementation of constructivist approaches to foster sustainable improvements in students' mathematical communication abilities.